1983
DOI: 10.1111/j.1432-1033.1983.tb07466.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Probable Involvement of Arginine Residues in the Bile‐Salt‐Binding Site of Human Pancreatic Carboxylic Ester Hydrolase

Abstract: Modification of arginine residues with 2,3-butanedione inhibits the carboxylic-ester hydrolase activity on soluble and emulsified substrates when assayed with bile salts. The a-dicarbonyl reagent modifies seven of the nineteen arginine residues present per enzyme molecule. Nevertheless the inactivation with butanedione is greatly diminished when the protein is in the presence of negatively charged micellar bile salt. In these conditions we observe the protection of one arginine residue by sodium taurodeoxychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…However, a bile-salt-mediated cross-binding of Tyr122 and Arg63 could induce a conformational change, especially as loop L,,,* (following Arg63) is probably not anchored by salt bridging in the carboxylester-lipase enzymes. The close vicinity and possible coupling of the non-specific site to the oxyanion hole loop (salmon carboxylester-lipase positions 105-113) may explain the increase in k,,, observed upon bile-salt-binding, especially with taurodeoxycholate [45].…”
Section: Hypothetical Bile-salt-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a bile-salt-mediated cross-binding of Tyr122 and Arg63 could induce a conformational change, especially as loop L,,,* (following Arg63) is probably not anchored by salt bridging in the carboxylester-lipase enzymes. The close vicinity and possible coupling of the non-specific site to the oxyanion hole loop (salmon carboxylester-lipase positions 105-113) may explain the increase in k,,, observed upon bile-salt-binding, especially with taurodeoxycholate [45].…”
Section: Hypothetical Bile-salt-binding Sitesmentioning
confidence: 99%
“…Binding of the hydroxy groups may be accomplished by Asnll7, Gln66 and Gln71, all carboxylester-lipase-conserved residues. However, niodelling studies showed that an involvement of the glutamine residues and Phe60 would require a different conformation of the shortened loop L,,,* and, to a certain extent, loop L:,+ A dimerization through this hypothetical site would bring the two non-specific sites together, and may explain the transformation of the non-specific site into a micellar and lipidbinding site [24,45,551. The possible bile-salt-binding mechanisms described in this study are summarized as a tentative model in Fig.…”
Section: Hypothetical Bile-salt-binding Sitesmentioning
confidence: 99%
“…Early studies have proposed that bile salts interact with two sites on the protein (2). One site, specific for primary bile salts, is associated with enzyme dimerization and activation, whereas the second is less specific, is able to bind indistinctly primary and secondary bile salts, and is involved in the enzyme binding to micellar or aggregated substrates (3,4). More recently, the presence of these two bile salt-binding sites has been detected on the human milk counterpart enzyme referred to as bile salt-stimulated lipase (5).…”
mentioning
confidence: 99%
“…Binding of a monomeric primary bile salt to the specific site leads to the opening of a loop comprised of residues His 115 to Tyr 125 of the bovine BSDL, a loop that otherwise is in a closed conformation which might hinder substrate binding (6,7). Using chemical modification approaches, tyrosine and arginine have been identified as key residues for BSDL interaction with bile salts (3,4). Furthermore, a recent study demonstrated that Arg 63 is essential for the enzyme activity on substrates such as cholesteryl oleate solubilized by sodium taurocholate (9).…”
mentioning
confidence: 99%
“…Early studies (2) have proposed that bile salts interact with two sites on the protein. One site, specific for primary bile salts, is associated with enzyme dimerization and activation, whereas the second site is less specific, able to bind indistinctly primary and secondary bile salts, and is involved in the enzyme binding to micellar or aggregated substrates (3,4). More recently the presence of these two bile salt-binding sites has been detected on the human milk counterpart enzyme referred to as bile salt-stimulated lipase (5).…”
mentioning
confidence: 97%